Experimental Verification of Kinematically Admissible Solutions for Incipient Stage of a Cohesive Soil Shoving Process - Szyba, D.; Trąmpczyński, W. (Engineering Transactions, 1994)
The results of an experimental investigation of kinematics of cohesive soil in the case of pushing rigid walls, shaped similarly to heavy machine tools, arc shown. The experiments were performed under plane strain conditions on a model material at several levels of preconsolidation. The experimentally observed mechanisms of soil deformation were determined photographically and confronted with theoretical solutions concerning incipient plastic motion. Solutions were obtained within the theory of plasticity, under the assumption of kinematically admissible mechanisms and associated flow rule, for a rigid-perfectly plastic Coulomb-Mohr material. A good agreement with theoretical solutions was obtained.